2019
DOI: 10.2478/geoca-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

The calcareous nannofossils and magnetostratigraphic results from the Upper Tithonian–Berriasian of Feodosiya region (Eastern Crimea)

Abstract: This article is concerned with nannofossil study of Tithonian–Berriasian sediments of Eastern Crimea. The NJT 16, NJT 17a, NJT 17b, NKT, and NK 1 nannofossil zones were determined. The occurrence of Nannoconus kamptneri minor, one of the potential marker-types of the Tithonian–Berriasian boundary (the base of the NKT Zone) of the Tethyan sequence in the Feodosiyan section is assigned here to the Pseudosubplanites grandis ammonite Subzone and the magnetic Chron M18n. The base of the NKT Zone is closer to the Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Here we con sider stratigraphically in dic a tive nannofossil FOs and not nannofossil biozones, as these are in a state of flux and have not yet sta bi lised: zones have some times been ap plied in pub li ca tions with out tak ing into ac count pub lished changes in the po si tions of marker spe cies, e.g. in Cri mea, Arkadiev et al (2019), cit ing and ap ply ing Bralower (1989) and Casellato (2010). Fig ure 8 shows how sev eral taxa used as zonal in di ces now have very dif fer ent po si tions and ages com pared to those that were firstly, and sub se quently, at trib uted to them.…”
Section: Mw Samples (Fig 1: Section 3)mentioning
confidence: 81%
See 3 more Smart Citations
“…Here we con sider stratigraphically in dic a tive nannofossil FOs and not nannofossil biozones, as these are in a state of flux and have not yet sta bi lised: zones have some times been ap plied in pub li ca tions with out tak ing into ac count pub lished changes in the po si tions of marker spe cies, e.g. in Cri mea, Arkadiev et al (2019), cit ing and ap ply ing Bralower (1989) and Casellato (2010). Fig ure 8 shows how sev eral taxa used as zonal in di ces now have very dif fer ent po si tions and ages com pared to those that were firstly, and sub se quently, at trib uted to them.…”
Section: Mw Samples (Fig 1: Section 3)mentioning
confidence: 81%
“…How ever, the ev i dence pro vided by nannofossil taxa gives age in di ca tions for the two, and this sug gests that the west ern sec tion is slightly lower in the Tithonian than the east ern out crop (which is only just be low the base of the Berriasian). Arkadiev et al (2019), in the 80 metres be low the same brec cia (their out crop 2922), found no stratigraphically in dic ative nannofossil. Though the up per 25 metres had yielded to Svobodová et al (2019a) a typ i cal late Tithonian as sem blage of Nannoconus infans, N. puer and N. globulus mi nor, Polycostella sp.…”
Section: Localitiesmentioning
confidence: 83%
See 2 more Smart Citations